Strains of lactic acid bacteria isolated from traditional Carpathian cheeses - I. M. Slyvka; O. Y. Tsisaryk; G. V. Dronyk; L. Y. Musiy (Regulatory Mechanisms in Biosystems, 2018)
Traditional national fermented products and cheeses are a source for the search for species and strains of lactic acid bacteria (LAB) which are not within the range of bacterial agents used in the dairy industry. Classical and modern genetic-molecular methods are used to identify LAB isolated from such products. The purpose of our work was isolation and identification of LAB from traditional Carpathian cheeses made from ewe's milk and the study of their technological properties. Three samples of cheese were selected for our research – one sample of brine cheese bryndza and one sample of budz (bryndza before salting), produced in the highlands of the Carpathians and one sample of buts, produced in the foothills zone. 106 cultures were isolated from the samples of cheese. Genus and species identification was completed using classical microbiological and molecular genetics methods. Based on the complex of tinctorial, cultural, physiological and biochemical indices, the LAB isolated were assigned to the following genera and species: Lactococcus spp. (26 cultures), including L. lactis (13 cultures) and L. garvieae (13 cultures); Lactobacillus spp. – L. plantarum (31 cultures); Enterococcus spp. – E. faecium (25 cultures); Leuconostoc spp. – L. mesenteroides (24 cultures). These results were confirmed by molecular genetics methods. The largest range of species was found in a sample of bryndza from the Carpathian highlands. The isolated cultures were studied according to technological properties – milk-coagulation activity, acid-forming ability and resistance to different concentrations of kitchen salt. Most strains of L. lactis ssp. lactis, L. plantarum and L. mesenteroides were active acid-forming agents and coagulated milk in 3–9 hours, while L. garvieae and E. faecium coagulated milk after more than 24 hours. More than 80% of cultures showed resistance to 4% of kitchen salt solution, E. faecium was observed to have the highest salt tolerance. The results of RAPD typing showed significant intra-species heterogeneity, which indicates the need for further research on identification of individual strains. In all samples of cheese, L. lactis, L. garvieae, E. faecium were detected, which shows that they are typical representatives within the traditional Carpathian bryndza. Particular attention was paid to E. faecium, as many researchers have indicated probiotic properties of individual strains, as well as the ability to synthesize volatile substances that enrich the flavor bouquet of cheeses. Today strains of E. faecium are involved in the bacterial composition of starter cultures for cheeses.